A canopy conundrum: can wind-induced movement help to increase crop productivity by relieving photosynthetic limitations? - Murchie, Erik H.; Gibbs, Jonathon; Burgess, Alexandra J. (Oxford University Press, 2019)
Wind-induced movement is a ubiquitous occurrence for all plants grown in natural or agricultural settings and in the context of high, damaging wind speeds it has been well studied. However, the impact of lower wind speeds (that do not cause any damage) on mode of movement, light transmission and photosynthetic properties has, surprisingly, not been fully explored. This is likely to be influenced by biomechanical properties and architectural features of the plant and canopy. A limited number of eco-physiological studies have indicated that movement in wind has the potential to alter light distribution within canopies, improving canopy productivity by relieving photosynthetic limitations. Given the current interest in canopy photosynthesis is timely to consider such movement in terms of crop yield progress. This opinion article sets out the background to wind-induced crop movement and argues that plant biomechanical properties may have a role in the optimisation of whole canopy photosynthesis via established physiological processes. We discuss how this could be achieved using canopy models.